Software Component Selection Based on Quality Criteria Using the Analytic Network Process - Shah Nazir; Sajid Anwar; Sher Afzal Khan; Sara Shahzad; Muhammad Ali; Rohul Amin; Muhammad Nawaz; Pavlos Lazaridis; John Cosmas (Abstract and Applied Analysis)
Component based software development (CBSD) endeavors to deliver cost-effective and quality software systems through the selection and integration of commercially available software components. CBSD emphasizes the design and development of software systems using preexisting components. Software component reusability is an indispensable part of component based software development life cycle (CBSDLC), which consumes a significant amount of organization’s resources, that is, time and effort. It is convenient in component based software system (CBSS) to select the most suitable and appropriate software components that provide all the required functionalities. Selecting the most appropriate components is crucial for the success of the entire system. However, decisions regarding software component reusability are often made in an ad hoc manner, which ultimately results in schedule delay and lowers the entire quality system. In this paper, we have discussed the analytic network process (ANP) method for software component selection. The methodology is explained and assessed using a real life case study.